2017
DOI: 10.3390/v9030047
|View full text |Cite
|
Sign up to set email alerts
|

A Pelagic Microbiome (Viruses to Protists) from a Small Cup of Seawater

Abstract: The aquatic microbiome is composed of a multi-phylotype community of microbes, ranging from the numerically dominant viruses to the phylogenetically diverse unicellular phytoplankton. They influence key biogeochemical processes and form the base of marine food webs, becoming food for secondary consumers. Due to recent advances in next-generation sequencing, this previously overlooked component of our hydrosphere is starting to reveal its true diversity and biological complexity. We report here that 250 mL of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…A recent analysis of viral metagenomic sequence data from 43 surface ocean sites identified ~5500 populations of dsDNA viruses, of which only 39 could be affiliated to cultured viruses [ 22 ]. Even at very small scales, viral diversity may be high, as demonstrated by Flaviani et al [ 25 ], who found 254 unique virus phylotypes in a 250 mL oceanic water sample, supporting previous suggestions that local viral diversity is relatively similar to global diversity [ 22 ].…”
supporting
confidence: 71%
“…A recent analysis of viral metagenomic sequence data from 43 surface ocean sites identified ~5500 populations of dsDNA viruses, of which only 39 could be affiliated to cultured viruses [ 22 ]. Even at very small scales, viral diversity may be high, as demonstrated by Flaviani et al [ 25 ], who found 254 unique virus phylotypes in a 250 mL oceanic water sample, supporting previous suggestions that local viral diversity is relatively similar to global diversity [ 22 ].…”
supporting
confidence: 71%
“…The development of long-read sequencing methods, preemptively deemed “third-generation sequencing”, may address many of the issues with short-read assembly and viral quantification. DNA barcoding has been suggested as a cheap, reliable method to quickly track virus populations, and has recently been shown to recapitulate general viral community structures using sample volumes no bigger than a cup of water [ 168 ]. New virus isolates can be discovered from sequencing of single aquatic viruses sorted by flow cytometry, [ 169 ], as closely related, hyper diverse viruses are suggested to be difficult to assemble from metagenomes [ 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the surface ocean, drastic changes in microbial species composition across space may point to strong changes in abiotic selection (as expected to occur across oceanographic fronts [74,75]), or high immigration. We identified 14 stations featuring abrupt changes in prokaryotic or picoeukaryotic community composition as well as 36 stations with a "unique" species composition.…”
Section: Discussionmentioning
confidence: 99%